Marketing Performance of Pomelo Oranges in Padang Lampe Village, Ma'rang District, Pangkajene Kepulauan Regency - Najib, Marhawati (PT. Maju Malaqbi Makkarana, 2024)
This study aims to determine the pattern of marketing channels and analyze the costs, margins profits, and economic efficiency of each pomelo orange marketing channel in Padang Lampe Village, Ma'rang District, Pangkep Regency. A sampling of producers was carried out by Simple Random Sampling while marketing institution samples using the tracing method or (snowball sampling) namely by tracing sales and purchases of pomelo oranges from producers to consumers. The results of the study showed that there are two types of marketing channels in Padang Lampe Village, Ma'rang District, Pangkep Regency, namely, channel I: Farmers——–Collectors ——— Inter-Island Traders ———– Retailers ————— Consumers. Furthermore, Marketing Channel II is from Farmers ———– Retailers ———– Consumers. In Marketing Channel I, the total marketing cost is IDR 25,660,000/7500 pomelo fruits, the total marketing margin is IDR 78,750,000/7500 fruits, and the total marketing profit is IDR 46,790,000. In Marketing Channel II, the total marketing cost is IDR 1,175,000/300 fruits, the marketing margin is IDR 2,250,000 and the total marketing profit is IDR 1,075,000. Marketing Channel II is the most efficient pomelo marketing channel because it has the lowest marketing margin, which is IDR. 2,250,000/300 pieces and has the highest Farmer's Share value, namely 57.14%.